Very high position resolution gamma imaging with resistive plate chambers - Blanco, A. (2006)
In this study we present experimental results from a first prototype of a positron emission tomography system based on the resistive plate chamber (RPC) technology. The system is composed of two counting heads, each one containing 16 single-gap RPC detectors capable of detecting the photon interaction point in the transaxial plane. Uniformity studies were performed for image resolution and sensitivity, yielding a rather uniform image resolution close to 0.3 mm FWHM across the field of view. The contribution of the photons noncolinearity effect to the intrinsic spatial resolution was also studied, causing a variation from 0.52 to 0.63 mm when the system diameter ranges from 60 to 120 mm, in agreement with calculations.